1990
DOI: 10.1128/aem.56.2.352-356.1990
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and biomass estimation of planktonic bacteria and viruses by transmission electron microscopy

Abstract: Bacteria and virus particles were harvested from water samples by ultracentrifugation directly onto Formvar-coated electron microscopy grids and counted in a transmission electron microscope. With this technique, we have counted and sized bacteria and viruses in marine water samples and during laboratory incubations. By X-ray microanalysis, we could determine the elemental composition and dry-matter content of individual bacteria. The dry weight/volume ratio for the bacteria was 600 fg of dry weight ,um-3. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
3
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(91 citation statements)
references
References 31 publications
3
81
3
4
Order By: Relevance
“…Head size distribution of viruses can vary with time and space [106,[159][160][161][162][163], however, not all of the studies have shown such changes [86,94,95,101]. Heterotrophic nanoflagellates are a major type of predators of prokaryotes in aquatic systems and their grazing is sizeselective, i.e., they graze preferentially on a particular size class [164,165].…”
Section: Morphological and Size Characteristicsmentioning
confidence: 99%
“…Head size distribution of viruses can vary with time and space [106,[159][160][161][162][163], however, not all of the studies have shown such changes [86,94,95,101]. Heterotrophic nanoflagellates are a major type of predators of prokaryotes in aquatic systems and their grazing is sizeselective, i.e., they graze preferentially on a particular size class [164,165].…”
Section: Morphological and Size Characteristicsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) is the most direct method for counting viral particles and can be Food Environ Virol (2015) 7:96-111 105 successfully used for determining the concentration of MS2 phage-like particles (Borsheim et al 1990). However, the long analysis time required, as well as the high cost and difficulty of this method has led to the development of alternative methods.…”
Section: Quantification Of Ms2 Phage-like Particlesmentioning
confidence: 99%
“…The clear lysate was centrifuged at 5000 g for 10 min to remove remaining cells and cell debris. When necessary, cyanophages were further concentrated either by precipitation with 10-15% (w ⁄ v) polyethylene glycol (PEG 6000, Fisher Scientific, Loughborough, U.K.) or by ultracentrifugation at 80 000 g for 120 min at 4°C (adapted from Børsheim et al, 1990) and resuspension of the pellet in 0.1· of the original volume of CP buffer.…”
Section: Cyanophage Concentrationmentioning
confidence: 99%
“…Viruses are the most abundant biological entities in aquatic systems (Suttle, 2005) and bacteriophages are the most common viruses (Børsheim, Bratbak & Heldal, 1990;Bratbak et al, 1990;Wommack & Colwell, 2000;Alonso et al, 2001). Given the numbers of cyanobacteria within the bacterioplankton, it may not be surprising to find that cyanophages are both widespread and abundant.…”
Section: Introductionmentioning
confidence: 99%